A method to evaluate the degree of bleaching of IRSL signals in feldspar: The 3ET method - Ivester, A.H.; Rhodes, E.J.; Dolan, J.F.; Van Dissen, R.J.; Gauriau, J.; Little, T.; McGill, S.F.; Tuckett, P.A. (Quaternary geochronology, 2022)
In addition to dating, IRSL luminescence signals can preserve information about erosional, transport, and depositional histories of a population of grains. Knowledge of the degree of bleaching can be useful in understanding the processes that occurred during previous depositional events, as certain transport conditions result in a well bleached signal, while others result in grains retaining an inherited signal from prior events. This information can be accessed by making single-grain IRSL measurements across successively increasing temperatures, thereby isolating signals from traps of different bleachabilities. A new approach offers a way to evaluate the completeness of bleaching of a grain by testing patterns of equivalent dose (DE) values measured at three elevated temperatures (3ET), 50, 125, and 225 °C. Consistent DE estimates across two or more temperatures suggest a single bleaching event of sufficient duration to fully depopulate the traps involved. Incompletely bleached grains with inconsistent DE values across temperatures will lack a 3ET “plateau.” Modes in the distribution of DE values for fully bleached grains can suggest depositional ages, subject to assessment of fading. We developed a Python code in a Jupyter Notebook environment for data analysis and visualization to expedite processing the large data sets produced by the 3ET protocol. The 3ET protocol was tested on a radiocarbon dated sequence of playa samples from California, USA and on a set of fluvial terraces in the Marlborough region of New Zealand as part of a larger project to reconstruct regional seismic history. Where standard pIRIR apparent ages can be inconsistent or ambiguous, 3ET age estimates produce generally consistent apparent ages. Modes of 3ET plateaus can be used to infer the most recent and prior events that resulted in a sub-population of grains being fully bleached. These initial results suggest that the 3ET method can be useful to characterize both the age and degree of bleaching of depositional events.